Location parameter estimation algorithm based on fractals theory for single mobile LMU - TIAN Zeng-shan; ZHOU Dong-sheng (Tongxin xuebao, 2007)
According to the diffculity of mobile station loction for third party,the location algorithm was designed for single LMU（location measurement unit）.The algorithm of fractal interpolation and signal strength different of three an-tenna was adopted to advance the location parameter precision.The Strobe correlator algorithm was introduced to miti-gate the multipath effect.The simulation result indicates the location algorithm can provide the high accuracy position.